(untitled) (Bangladesh Journal of Botany, 2026)
This study evaluated the effects of Chlorella vulgaris supplementation on oxidative stress, erythrogram, and leukogram parameters in 378 Gallus gallus domesticus (hens) assigned to six groups: control (C) and experimental (G1-G5). Over 71 days, blood samples were analyzed for serum metabolites, plasma minerals, antioxidant markers [glutathione (GSH), catalase (CAT), superoxide dismutase (SOD), total antioxidant capacity (TAC), protein carbonyl (PCO), malondialdehyde (MDA)], and hematological profiles. Chlorella supplementation significantly enhanced TAC, SOD, and GSH, while reducing MDA and PCO in a dose-dependent manner. Erythrocyte and leukocyte profiles also improved, indicating strengthened antioxidant defenses and immune responses, with higher doses exerting greater effects. Molecular docking further confirmed nutrient efficiency through interactions between isoquinoline and 3S3Q protein. Bangladesh J. Bot. 55(2): 371-379, 2026 (June)